Doppler Ultrasonography Derived Maximal Systolic Acceleration: Value Determination With Artificially Induced Stenosis. (July 2022) - Brouwers, Jeroen J. W. M.; van Doorn, Louk P.; Pronk, Laurie; van Wissen, Rob C.; Putter, Hein; Schepers, Abbey; Hamming, Jaap F.
Background: In diagnosing peripheral arterial disease (PAD), medial arterial calcification (MAC) hampers arterial compression and could lead to unreliable ankle brachial index (ABI), toe brachial index (TBI) and toe pressure (TP). Doppler ultrasonography (DUS) derived maximal systolic acceleration (ACCmax) might be more accurate to diagnose PAD. In an in vitro study, a strong correlation between ACCmax and the severity of stenotic disease was determined. The aim of this study was to investigate the ACCmax in correlation with conventional non-invasive diagnostics in an in vivo setting.Methods: In twelve healthy individuals, an arterial stenosis was mimicked by compression on the common femoral artery by an ultrasounds probe, creating a local stenosis of 50%, 70% and 90%. The ABI, TBI, TP and several DUS parameters (including ACCmax) were assessed at the ankle during these different degrees of stenosis. All DUS parameters were measured separately by two observers to determine the interobserver variability.Results: Overall the ABI, TBI, TP, ACCmax, ACCsys and PSV decreased significantly when the degree of stenosis increased. The ACCmax showed the highest correlation with the degree of stenosis (r −.884), compared to ABI (r −.726), TBI (r −.716) and TP (r −.758). Furthermore, the interobserver variability of ACCmax was excellent, with an intraclass correlation coefficient (ICC) of .97.Conclusion: ACCmax is an accurate non-invasive DUS parameter to diagnose and assess the severity of a mimicked arterial stenosis in healthy individuals. Further prospective assessment of the clinical value of ACCmax and its potential benefits in patients with PAD is needed.